2013
DOI: 10.1007/s10725-013-9796-5
|View full text |Cite
|
Sign up to set email alerts
|

Different relative humidity conditions combined with chloride and sulfate salinity treatments modify abscisic acid and salicylic acid levels in the halophyte Prosopis strombulifera

Abstract: It has been shown that abscisic acid (ABA) and salicylic acid (SA) act as endogenous signal molecules responsible for inducing abiotic stress tolerance in plants. However, our knowledge on the role of both phytohormones in response to environmental conditions in halophytic plants is still limited. In this study endogenous ABA and SA levels, growth parameters and chlorophylls content were determined in leaves and roots of the halophyte Prosopis strombulifera cultivated under increasing NaCl and Na 2 SO 4 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Besides, some toxic metabolites can be degraded to the inorganic sulfate in the medium of moderately high sulfate ion concentration (50-100 mM Na 2 SO 4 ) (Shevyakova 1981). In the current study, plant growth responded differently to NaCl and Na 2 SO 4 stress (Table 1), which appeared to be species specific as observed in previous studies (Franklin et al 2002;Colla et al 2012;Devinar et al 2013). It was found that Clposed a greater interfering effect on plant development and water balance than SO 4 2- (Rogers et al 1998).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Besides, some toxic metabolites can be degraded to the inorganic sulfate in the medium of moderately high sulfate ion concentration (50-100 mM Na 2 SO 4 ) (Shevyakova 1981). In the current study, plant growth responded differently to NaCl and Na 2 SO 4 stress (Table 1), which appeared to be species specific as observed in previous studies (Franklin et al 2002;Colla et al 2012;Devinar et al 2013). It was found that Clposed a greater interfering effect on plant development and water balance than SO 4 2- (Rogers et al 1998).…”
Section: Discussionsupporting
confidence: 80%
“…With salinity level at the same equimolar concentration, sulfate is less toxic to jack pine (Franklin et al 2002), pea (Hamdia and Shaddad 1996) and lucerne (Medicago sativa L.) (Rogers et al 1998). On the contrary, growth of Cornus stolonifera Michx (Renault et al 2001), Ocimum basilicum (Tarchoune et al 2010) and Prosopis strombulifera (Devinar et al 2013) decreased strongly in plants treated with Na 2 SO 4 than in plants treated with NaCl of the same molar concentration.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These plant hormones are considered as the most vital elements that are critical in controlling physiological responses in plant under salt stress environment (Khan and Khan 2013). ABA ABA is considered as the stress hormone because it effect internal signaling of plant against adverse environment, and plays a vital role throughout the plant life cycle and facilitates plant reactions to different abiotic and biotic stresses (Keskin et al 2010;Devinar et al 2013). ABA biosynthesis increased in rice under osmotic stress due to salt accumulation (Kumar et al 2013).…”
Section: Effects On Nutrient Accumulation and Transportmentioning
confidence: 99%
“…In fact, NaCltreated plants accumulated similar levels of Na+ than Na 2 SO 4 -treated plants in their leaves, but they succeeded in ion compartmentalization and osmoregulation with direct consequences on their growth; these plants showed the lowest levels of SA. This response suggests that SA production is not a protective hormonal signal like ABA but a signal of injury in P. strombulifera under these adverse conditions (Devinar et al, 2013).…”
Section: Introductionmentioning
confidence: 94%